2016
DOI: 10.1089/cap.2015.0022
|View full text |Cite
|
Sign up to set email alerts
|

Developing Rapport and Therapeutic Alliance During Telemental Health Sessions with Children and Adolescents

Abstract: Objective: The purpose of this study was to describe the special considerations for building rapport and establishing a therapeutic alliance when conducting mental health evaluations for children and adolescents via videoconferencing. Methods: The authors review the literature and describe their experience in conducting mental health evaluations, developing rapport, and establishing a therapeutic alliance during telemental health practice. Results: Clinical need and shortages of clinicians with expertise in ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 41 publications
2
50
0
Order By: Relevance
“…It is noteworthy that clients’ inability to attend office-based treatment was the barrier (i.e., item on the Barriers to Child Trauma Treatment measure) most commonly reported both before and after the CBLCs. This finding suggests that innovative methods of treatment service delivery–such as community-based services (e.g., de Arellano, Waldrop, Deblinger, Cohen, Danielson, & Mannarino, 2005), integrated behavioral health care (Meadows Mental Health Policy Institute, 2016), use of tablets or iPads (Ruggiero, Saunders, Davidson, Cook & Hanson, in press) and telehealth services (Comer et al, 2015; Gloff, LeNoue, Novins, & Myers, 2015; Goldstein & Glueck, 2016)–may offer viable ways to increase access to treatment for abused and traumatized children. As one particularly relevant example, a recent study by Stewart and colleagues (2017) indicated that Trauma-Focused Cognitive Behavioral Therapy (Cohen et al, 2017), a child-focused EBT for trauma-related mental health problems, delivered via telehealth achieved treatment effects that were comparable to treatment delivered in an in-person, office-based setting, providing preliminary evidence for a promising approach to overcome service access barriers.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that clients’ inability to attend office-based treatment was the barrier (i.e., item on the Barriers to Child Trauma Treatment measure) most commonly reported both before and after the CBLCs. This finding suggests that innovative methods of treatment service delivery–such as community-based services (e.g., de Arellano, Waldrop, Deblinger, Cohen, Danielson, & Mannarino, 2005), integrated behavioral health care (Meadows Mental Health Policy Institute, 2016), use of tablets or iPads (Ruggiero, Saunders, Davidson, Cook & Hanson, in press) and telehealth services (Comer et al, 2015; Gloff, LeNoue, Novins, & Myers, 2015; Goldstein & Glueck, 2016)–may offer viable ways to increase access to treatment for abused and traumatized children. As one particularly relevant example, a recent study by Stewart and colleagues (2017) indicated that Trauma-Focused Cognitive Behavioral Therapy (Cohen et al, 2017), a child-focused EBT for trauma-related mental health problems, delivered via telehealth achieved treatment effects that were comparable to treatment delivered in an in-person, office-based setting, providing preliminary evidence for a promising approach to overcome service access barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that services delivered via telehealth are as effective as office-based treatment in addressing a number of disorders in youth such as attention deficit hyperactivity disorder (ADHD) (Myers, Vander-Stoep, Zhou, McCarty, & Katon, 2015), obsessive-compulsive disorder (OCD) (Comer et al, 2014), disruptive and oppositional behavior (Comer et al, 2015), depression (Nelson, Barnard, & Cain, 2003), and other mental health problems (see Gloff et al, 2015 for a review). Telehealth has also been shown to be acceptable among youth and their parents, with research suggesting that clinicians and patients are able to establish a positive therapeutic alliance that closely approximates face-to-face treatment (Goldstein & Glueck, 2016). Parents, youth, and referring providers report high levels of satisfaction with the care received (Hilty et al, 2016; Myers, Palmer, & Geyer, 2011).…”
Section: Research Supporting Telemental Healthmentioning
confidence: 99%
“…A literature review focusing on the client–therapist relationship in TMH identified 23 studies that indicate that a strong therapeutic alliance can be established through TMH services that is comparable to the alliance formed in face-to-face psychotherapy encounters (Simpson & Reid, 2014). Some studies report that children, adolescents, and their families like and often prefer TMH rather than face-to-face sessions based on rapport with therapist (Goldstein & Glueck, 2016). Combat veterans with PTSD also report a preference for in-home TMH services citing privacy and avoidance of busy clinics with long wait times (Hilty et al 2013; Moreland, Greene, Ruzek, & Godleski, 2016).…”
Section: Evidence For Telemental Health Outcomesmentioning
confidence: 99%